Antiproliferative effect of a lectin- and anti-Thy-1.2 antibody-targeted HPMA copolymer-bound doxorubicin on primary and metastatic human colorectal carcinoma and on human colorectal carcinoma transfected with the mouse Thy-1.2 gene - Ríhová, B; Jelínková, M; Strohalm, J; St'astný, M; Hovorka, O; Plocová, D; Kovár, M; Dráberová, L; Ulbrich, K (Bioconjugate chemistry, 2000)
The aim of this study was to compare the potential of two plant lectins [peanut agglutinin (PNA) and wheat germ agglutinin (WGA)], monoclonal antibody (anti-Thy-1.2), its F(ab')(2) fragments, and galactosamine as targeting moieties bound to the polymer drug carrier to deliver a xenobiotic, doxorubicin, to selected cancer cell lines. We have used primary (SW 480, HT 29) and metastatic (SW 620) human colorectal cancer cell lines and a transfectant, genetically engineered SW 620 cell line with mouse gene Thy-1.2 (SW 620/T) to test the possibility of marking human cancer with xenogeneic mouse gene and use it for effective site-specific targeting. The targeting moieties and doxorubicin were conjugated to a water-soluble copolymer based on N-(2-hydroxypropyl)methacrylamide (HPMA) acting as a carrier responsible for controlled intracellular release of the targeted drug. FACS analysis showed a strong binding of WGA-FITC to all tested cell lines. Binding of PNA-FITC was considerably weaker. The in vitro antiproliferative effect of lectin-targeted HPMA carrier-bound doxorubicin evaluated as [(3)H]TdR incorporation reflected both the intensity of the binding and the different sensitivity of the tested cancer cells lines to doxorubicin. The antiproliferative effect of conjugates targeted with WGA was comparable to that with the conjugates targeted with the anti-Thy-1.2 monoclonal antibody or their F(ab')(2) fragments. The magnitude of the cytotoxic effect of HPMA-doxorubicin targeted with PNA was lower in all tested cell lines. While the conjugates with WGA were more cytotoxic, the conjugates with PNA were more specific as their binding is limited to cancer cells and to the sites of inflammation. Noncytotoxic conjugates with a very low concentration of doxorubicin and targeted with PNA, anti-Thy-1.2, or their F(ab')(2) fragments exerted in some lines (SW 480, SW 620) low mitogenic activity. The Thy-1.2 gene-transfected SW 620 metastatic colorectal cancer cell line was sensitive to the antiproliferative effect of Thy-1.2-targeted doxorubicin as was shown for the Thy-1. 2(+) EL4 cell line and for Thy-1.2(+) concanavalin A-stimulated mouse T lymphocytes. These results represent the first indication of the suitability of transfection of human cancer cells with selected targeting genes for site-specific therapy of malignancies.
Keywords: buněčné dělení; Animals; Doxorubicin; Thy-1 Antigens; Methacrylates; kolorektální nádory; Wheat Germ Agglutinins; aglutinin z podzemnice olejné; imunoglobuliny - Fab fragmenty; methakryláty; Colorectal Neoplasms; indikátory a reagencie; transfekce; Antibodies, Monoclonal; Lymphocyte Activation; Transfection; aktivace lymfocytů; lidé; rekombinantní proteiny; Recombinant Proteins; Immunoglobulin Fab Fragments; Mice; nádorové buňky kultivované; Peanut Agglutinin; Indicators and Reagents; T-lymfocyty; myši; Tumor Cells, Cultured; doxorubicin; antigeny Thy-1; monoklonální protilátky; T-Lymphocytes; zvířata; Cell Division; aglutininy z pšeničných klíčků; Humans